Analisis Strategi Personal Selling Produk Zara Dalam Meningkatkan Volume Penjualan Sektor Produk Global - Chadisa Rizky Ananda; Suhairi Suhairi; Diah Ananda Kharisma; Dona Zahra Hasibuan; Yuda Pratama (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Sales competition in a global market has increased. At present there are many competitors from various types of companies that have various strategies to increase sales volume and increase their popularity among the public or consumers. This causes the need for a strategy in marketing, one of which is personal selling. This study aims to analyze the form of the strategy carried out by the Zara brand by using personal selling to increase sales volume in the global market. The research method used is descriptive research with a qualitative type. The primary data source used is information that contains information about zara's personal selling marketing as well as several supporting references as secondary data sources. The results of the study show that Zara itself divides consumers into three types as an initial strategy in carrying out personal selling activities. Some of the steps taken by Zara in carrying out personal selling are by approaching customers, providing directions for customers and finding alternatives or solutions to problems experienced by customers. Keyword: Personal Selling, Sales Volume, Zara